(untitled) (Research, Society and Development, 2017)
Industrial restaurants generate, when preparing and serving meals, a number of wastes that are administered in different ways. However, increasing waste generation leads to the need of establishing measures capable of permanently control the environmental effects of the entire production process. In this sense, this work aimed at verifying the generation of organic residues from the industrial restaurant of Cauê Mine, located in the Itabira/MG Mining Complex, as well as to evaluate if the technologies currently used for the management of these wastes are environmentally sustainable and economically viable. Thus, it was sought to identify the foods responsible for their higher generation, resulting in the alteration of the menu and, consequently, a reduction of 81.85% of organic residues. Another important factor was the reuse of fruit peels in desserts, providing healthier foods and reducing the amount of waste sent to the final treatment. Regarding the final disposal of organic waste in the landfill, it was observed that during the analyzed period there was a reduction of 64.67% of the values initially paid. In the aspect related to waste, it was found that the campaigns developed aiming at the "zero waste" of both restaurant staff and customers, also had a positive influence on the reduction of residual "ingestion" waste.